Antidermatophyte Activity of the Essential oil of Hypericum perforatum of North of Iran - M Larypoor; A Akhavansepahy; N Rahimifard; H Rashedi (Institue of Medicinal Plants, ACECR, 2009)
Background: Dermatophytes are the main cause of human superficial mycosis that is still a public health problem especially in tropical countries such as Iran. Objective: The aim of this study was determining the antifungal effect of Hypercom perforatum essential oil. Methods: The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) for the essential oil of the plant Hypericum perforatum against various dermatophytes were determined. The essential oil of Hypericum perforatum was obtained by hydro distillation of the dried plant. Clinical isolates of dermatophytes (Epidermophyton floccosum, Microsporum canis, Microsporum gypseum, T. mentagrophytes var. interdigital, T. mentagrophytes var. mentagrophytes., T. rubrum and Trichophyton tonsurans) were used for determining antifungal activity of this essential oil by in vitro tube dilution technique. Results: MIC90 and MFC90 values were remarkable. T. mentagrophytes var. interdigital showed a>1 log10 difference in viable count between treatment and control within the first hour, whereas E. floccosum did not. The essential oil of H. perforatum sufficiently inhibited and killed all tested dermatophytes in all different dilutions. The changes in growth curve of the treated dermatophytes were significant compared with the untreated dermatophytes. Conclusion: Terpinen-4-ol is the main component of the essential oil of H. perforatum, and perhaps could play the important role in antidermatophyte activity among the other components. It is suggested trying the in-vivo effects of Hypericum perforatum ointment or its other medicinal forms in the treatment and controlling of dermatophytes infections.